Nanoporous Polyether Sulfone Membrane, Preparation and Characterization: Effect of Porosity and Mean Pore Size on Performance - Salehi Shahrabi, Sara; Reza Mortaheb, Hamid; Barzin, Jalal; Reza Ehsani, Mohammad (Journal of Membrane and Separation Technology, 2017)
Flat sheet membranes were prepared by phase inversion technique using polyether sulfone (PES) dissolved in dimethylacetamide (DMAc) with and without adding polyvinylpyrrolidone (PVP) or polyethyleneglycol (PEG). The characteristics of the prepared membranes were evaluated using Scanning Electron Microscope (SEM) images, Atomic Force Microscopy (AFM), and Optical Contact Angle (OCA) measurements, and porosity tests. The porosity test and SEM images show that increasing additives to a certain value increases the porosity of the membrane. Also, as the coagulation bath temperature is increased, the porosity of the membrane is increased. The roughness of the membrane is increased by increasing the additive concentration. The analysis of AFM images confirms the nanoporous structure of the prepared membranes, and that the membranes with appropriate pore size distribution can be prepared by the applied method. Permeability tests using single-layer membranes show that the direct relationship between porosity and the flux of pure water or salt solution is dominated by the effect of applied additive while the salt rejection shows an inverse relationship with the mean pore size regardless of the applied additive. The salt permeation flux is a function of total porosity while the salt rejection is a function of surface porosity. Pervaporation tests show that both permeation flux and enrichment factor depend on the total porosity of the support membrane.